2010
DOI: 10.1007/s11130-010-0175-3
|View full text |Cite
|
Sign up to set email alerts
|

Protective Role of Three Vegetable Peels in Alloxan Induced Diabetes Mellitus in Male Mice

Abstract: The hitherto unknown glucose regulating role of three vegetable peels from cucurbitaceae family was evaluated. In a preliminary study, effects of ethanolic extracts of Cucurbita pepo, Cucumis sativus and Praecitrullus fistulosus peels were studied at 250 and 500 mg kg(-1) d(-1) for 15 days in the alterations in serum glucose and in hepatic lipid peroxidation (LPO) in male mice. In the pilot experiment, the effective and safe concentration of each peel was administered (p.o.) for 10 consecutive days and then on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
29
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(35 citation statements)
references
References 26 publications
5
29
0
1
Order By: Relevance
“…Diabetes was confirmed 48 hours after alloxan injection by determining the plasma glucose concentra-tion; only animals with plasma glucose of 150 -200 mg/dL were used for the experiment. The diabetic animals were allowed free access to tap water and pellet diet and were maintained at room temperature in plastic cages (Dixit and Kar, 2010).…”
Section: Induction Of Experimental Diabetesmentioning
confidence: 99%
“…Diabetes was confirmed 48 hours after alloxan injection by determining the plasma glucose concentra-tion; only animals with plasma glucose of 150 -200 mg/dL were used for the experiment. The diabetic animals were allowed free access to tap water and pellet diet and were maintained at room temperature in plastic cages (Dixit and Kar, 2010).…”
Section: Induction Of Experimental Diabetesmentioning
confidence: 99%
“…In addition, C. ficifolia reduced plasma and liver triglycerides (TG) levels by 47% and 15%, respectively. Moreover, serum TC and atherogenic index were significantly lower in the C. ficifolia group than in controls (P < 0.05) (14). Makni et al (8) showed the serum TG level did not differ between the control and pumpkin groups although the nonesterified fatty acid (NEFA) level was significantly lower in the C. ficifolia group in comparison with the control group (P < 0.05) (15).…”
Section: Resultsmentioning
confidence: 97%
“…Another study found that both plasma and liver lipids decreased by 21% and 19%, respectively, in the group of animals with C. ficifolia diet (14). Xia et al (10) reported that C. ficifolia -rich diet reduced plasma and liver total cholesterol (TC) levels by 47% and 45%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In animal models of both T1D and T2D, polyphenols of different origin were reported to lower blood glucose levels (Al-Awwadi et al 2004;Su, Hung, and Chen 2006;Ciocoiu et al 2009;Dixit and Kar 2010;Ong et al 2011). The hypoglycemic effect can be caused by multiple mechanisms.…”
Section: Wwwintechopencommentioning
confidence: 99%
“…This may be a result of direct antioxidant activity of polyphenols, as well as a result of their ability to upregulate expression of antioxidant-defense enzymes: glutathione peroxidase (GSHPx) superoxide dismutase and catalase activities (Ciocoiu et al 2009;Lee, Wang, et al 2009;Dixit and Kar 2010). It is well known that oxidative stress plays a substantial role in the destruction of beta-cells by infiltrated self macrophages and lymphocytes.…”
Section: Wwwintechopencommentioning
confidence: 99%